Experimental Investigation on Mechanical Properties of Cemented Paste Backfill under Different Gradations of Aggregate Particles and Types and Contents of Cementing Materials - Jiangyu Wu; Meimei Feng; Guansheng Han; Xiaoyan Ni; Zhanqing Chen (Advances in Materials Science and Engineering)
Obtaining the optimal gradation of aggregate particles is beneficial for improving the strength of cemented paste backfill (CPB). Consequently, the uniaxial compression tests with acoustic emission (AE) monitoring were performed on CPB, for which the aggregate particles satisfied the Talbot grading theory. The effects of the Talbot indices of aggregate particles and types and contents of cementing materials on the mechanical properties of CPB were analyzed. The AE characteristics and stress-strain behaviors of CPB were discussed. The results show that the specific Talbot index reflected the optimal strength and deformation properties of CPB is 0.45, and the maximum UCS is 7.6 MPa. The mechanical properties of CPB also can be optimized by changing the type of cementing material and increasing the content of cementing material. The effects of the Talbot indices of aggregate particles and types and contents of cementing materials on the crack damages reflected by the AE signals of CPB are mainly observed in the oa stage and ab stage during the loading process.